The Position of the Concept and Theory of Equilibrium in Islamic Economics (A Brief Comparison of the Application of this Concept in Conventional Economics and the View of Shahid Sadr in his Book Our Economy “Iqtisaduna”) - Mohammad Hussein Karami Asafeh; Hussein Bahraini Yazdi (جستارهای اقتصادی, 2021)
The concept and theory of equilibrium in conventional economics is one of the central points in economic theory. The relationship between the concept of equilibrium and the coordination of economic individuals' behavior is a key point in understanding the equilibrium theory i.e., in the market system, to achieve collective interest without the direct intervention of governments. In many works on Islamic economics, monetary and real equilibrium in different markets have been extracted without mentioning the basis of this concept. In fact, it has been viewed with a value perspective. After a brief overview of the concept of equilibrium in conventional economics, this article goes on to concisely discuss equilibrium application in works on Islamic economics. The main idea of the article is that if people's interaction with each other and the theory of government intervention in Islamic economics is not clarified, speaking of equilibrium in the conventional sense is a kind of misplaced assumption. In some works, such as  Iqtisaduna "Our Economy"a book by Muhammad Baqir al-Sadr, one can find important distances with an equilibrium perspective. An alternative approach can be seen due to the presentation of a different picture of government intervention and people participation in the economy. The present paper dealt with this important issue by reviewing and comparing texts.